Efficacy of Microwave-Heating during Alkaline Processing of Fumonisin-Contaminated Maize. - Abraham Mendez-Albores; Denisse Anelem Cardenas-Rodriguez; Alma Vazquez-Duran (Tehran University of Medical Sciences, 2014)
Fumonisins (a family of foodborne carcinogenic mycotoxins) cause health hazards to humans and animals in developing countries, and has also economic implications. Therefore, the efficacy of a novel environmental friendly nixtamalization procedure to make tortillas (the main staple food for the Mexican population) was investigated.Maize contaminated with 2136.67 ng/g total fumonisins was processed into tortillas, starting with maize grits mixed with water and calcium hydroxide that was cooked in a microwave field at 2.45 GHz during 3.75 min, and steeped 3.5 h at room temperature. The steeped maize grits (nixtamal) was stone-ground into masa (maize dough), which was then used to make tortillas. Total fumonisin content was determined using monoclonal antibody columns.Masa contained 1998.33 ng/g total fumonisins, which represents 6.5% toxin reduction. Nevertheless, fumonisin concentration was reduced significantly in tortillas (up to 985.33 ng/g) due to the cooking process, corresponding to a cumulative toxin degradation of 54%. Tortillas were below the maximum tolerated level, considering the European Union regulatory limit for fumonisins in maize (1000 ng/g). The physicochemical and technological properties of tortillas were also considered within the acceptable margins of quality.Microwave nixtamalization was not a feasible method to reduce fumonisin content in masa to acceptable levels; however, an effective extra-reduction occurred when masa was baking into tortillas.